Thesium ovatifolium (Santalaceae), a new species with ovate leaves from KwaZulu-Natal, South Africa - Lombard, Natasha; Le Roux, M. Marianne; van Wyk, Ben-Erik (Phytotaxa, 2019)
A new species from South Africa, Thesium ovatifolium, is described. A diagnosis, description and photographs are provided along with details of its distribution, habitat and conservation status. The new species forms part of Thesium sect. Barbata, which is characterized by the presence of a dense apical beard on the corolla lobes and post-staminal hairs connecting the anthers to the perianth. It is distinguished by its alate stems, large ovate leaves and bracts, with reticulate secondary venation, 3- to 4-flowered cymes on inflorescence apices, as well as the rosulate arrangement of leaves and bracts in young stems and inflorescences. Thesium ovatifolium is believed to be Endangered (EN), based on IUCN criteria.